Bio-potential of fermented fruits waste solutions on in vitro seed germination and regeneration of Lycium barbarum and Aquilaria malaccensis Lamk. - Farida Jaafar,; Asmah Awal,; Shamsiah Abdullah,; Fauziah Ismail,; Norrizah Jaafar Sidik,; Noor Azma Yusuf, (Penerbit Universiti Kebangsaan Malaysia, 2015)
There are many synthetic growth media for plant tissue culture available in the market such as Murashige and Skoog (MS) Medium, Woody Plant Medium (WPM), Schenk and Hildebrandt (SH) Medium and Gamborg’s B-5 Medium. The aim of this study was to substitute the synthetic media used in the plant tissue culture by organic additives which are pineapple, banana, papaya, calamansi lime, kaffir lime and key lime peels. Two formulated fermented fruits waste solutions composed of these organic additives were prepared in different concentrations (Formula A- calamansi lime, kaffir lime, and key lime peel; Formula B -banana, pineapple, and papaya peels) to study their effects on in vitro seed germination and regeneration of Lycium barbarum and Aquilaria malaccensis Lamk. Statistical results showed that they were significantly different in interaction effects (p<0.05) in promoting the plant growth in the formulated media as compared to control medium determined by ANOVA test. Application of this formulated fermented fruits waste solutions should be considered since it is found to be responsive in in vitro seed germination and regeneration of L. barbarum and A. malaccensis Lamk and will potentially minimize the operational cost.